Elucidating and Mitigating High‐Voltage Degradation Cascades in Cobalt‐Free LiNiO2 Lithium‐Ion Battery Cathodes. Issue 3 (19th November 2021) - Park, Kyu‐Young; Zhu, Yizhou; Torres‐Castanedo, Carlos G.; Jung, Hee Joon; Luu, Norman S.; Kahvecioglu, Ozge; Yoo, Yiseul; Seo, Jung‐Woo T.; Downing, Julia R.; Lim, Hee‐Dae; Bedzyk, Michael J.; Wolverton, Christopher; et al.
Abstract: LiNiO2 (LNO) is a promising cathode material for next‐generation Li‐ion batteries due to its exceptionally high capacity and cobalt‐free composition that enables more sustainable and ethical large‐scale manufacturing. However, its poor cycle life at high operating voltages over 4.1 V impedes its practical use, thus motivating efforts to elucidate and mitigate LiNiO2 degradation mechanisms at high states of charge. Here, a multiscale exploration of high‐voltage degradation cascades associated with oxygen stacking chemistry in cobalt‐free LiNiO2, is presented. Lattice oxygen loss is found to play a critical role in the local O3–O1 stacking transition at high states of charge, which subsequently leads to Ni‐ion migration and irreversible stacking faults during cycling. This undesirable atomic‐scale structural evolution accelerates microscale electrochemical creep, cracking, and even bending of layers, ultimately resulting in macroscopic mechanical degradation of LNO particles. By employing a graphene‐based hermetic surface coating, oxygen loss is attenuated in LNO at high states of charge, which suppresses the initiation of the degradation cascade and thus substantially improves the high‐voltage capacity retention of LNO. Overall, this study provides mechanistic insight into the high‐voltage degradation of LNO, which will inform ongoing efforts to employ cobalt‐free cathodes in Li‐ion battery technology. Abstract : Lattice oxygen loss is found to play a critical role in the O3–O1 stacking transition in cobalt‐free LiNiO2 lithium‐ion battery cathodes, which subsequently induces Ni‐ion migration and irreversible stacking faults, microscale creep, cracking, and even bending of layers after high‐voltage cycling. By suppressing oxygen evolution, hermetic graphene coatings arrest this degradation cascade, resulting in substantially improved high‐voltage capacity retention.